Окремі проблеми волевиявлення у ході виникнення договірних суб’єктивних цивільних прав - Погребняк, В.; Pohrebniak, V. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
Стаття присвячена розгляду ролі волевиявлення у ході виникнення суб’єктивних цивільних прав при формуванні договірного цивільного правовідношення. Автор розглядає проблему укладення договору за рішенням суду, а також аналізує сучасні тенденції практики правореалізації в частині оформлення договорів. Формується висновок про те, що механізм укладення договорів за рішенням суду, який знайшов відображення на рівні положень Господарського кодексу України, може бути впроваджений і на рівні Цивільного кодексу України. The article highlights the role of the expression of will concerning the subjective civil rights emergence in the course of the contract civil legal relations formation. The author focuses on the issue of concluding a contract by a court decision and analyzes the current trends in the practice of law enforcement in terms of contract engrossment. The article considers the appropriate legal scheming of contract from the standpoint of the principle of freedom of will and the free expression of will, including the law enforcement practice context of the highest courts in Ukraine. The author concludes that the mechanism of concluding agreements/contracts by a court decision, which reflects mainly the provisions of Commercial Code of Ukraine, can be applied at the level of Civil Code of Ukraine since it harmoniously fits into the legal protection system concerning the subjective civil rights and may positively influence their legal support level.
Some Issues of the Expression of Will in the Contractual Subjective Civil Rights
Keywords: виникнення прав; укладення договору; форма договору; право вимоги; рішення суду; origin of rights; concluding a contract; form of contract; right of claim; court decision